(untitled) (Washington, D.C., 2006)
Continuing globalization, and the opportunity for states in transition to benefit from it, will depend heavily on the training and education of the immediate and future workforce. At present nations of East Asia and Latin America commit relatively few resources to secondary education, resulting in unmet demand, low accountability of service delivery, poor teacher performance, and costly curricular structures, although many are taking steps toward reform with programs in place. Emphasizing policies and practices which reinforce positive change, this report details the trends and challenges in Latin American and East Asian secondary education, the demand in terms of the labor market and incentives to meet that demand, financial challenges in the next decade, and methods of measuring and improving the efficiency of secondary education. Appendices include empirical data and information on demographics and secondary school structures
Keywords: Education, Seconday,Educational change,Education, Seconday,Educational change; Latin America,Latin America.,East Asia.,East Asia